Intestinal clostridial counts have no diagnostic value in the diagnosis of enterotoxaemia in veal calves. (2nd March 2013) - Valgaeren, B. R.; Pardon, B.; Verherstraeten, S.; Goossens, E.; Timbermont, L.; Haesebrouck, F.; Ducatelle, R.; Deprez, P. R.; Van Immerseel, F.
Abstract : Enterotoxaemia is an important cause of sudden death in veal calves. This study aimed to evaluate intestinal Clostridium perfringens counts as a diagnostic tool for enterotoxaemia. Field necropsies were conducted on 48 sudden death cases in Belgian Blue veal farms. In 31/48 suddenly deceased calves, the diagnosis of enterotoxaemia was made based on haemorrhagic lesions in the small intestines, while in seven of these cases, no clear‐cut diagnosis could be made based on macroscopic appearance of the gut. In the 10 remaining calves, a definitive cause of death other than enterotoxaemia could be identified. Samples of the intestinal content were taken for quantification of C perfringens . After matching cases and controls for diet, and the interval between death and sampling, no significant differences could be detected between the mean C perfringens counts of the small intestines in enterotoxaemia cases and counts in the matching segments in the control group. These results indicate that intestinal C perfringens counts cannot be advised as a discriminative postmortem diagnostic tool for enterotoxaemia in veal calves, not even when sampled within three hours after death.